2016
DOI: 10.1002/sdtp.11058
|View full text |Cite
|
Sign up to set email alerts
|

P-174: Pulse Width Modulation IGZO Gate on Array Structure for OLED Driving

Abstract: A novel gate driver on array (GOA) circuit topology based on pulse width modulation (PWM) technique has been proposed for internal compensation AMOLED pixel driving. The output width of PWM GOA basic unit can be easily adjusted by tuning start pulse (STU) signal width. The performance of this circuit has been verified by simulation and the prototype has been fabricated in 5 inch AMOLED panel with IGZO TFT process. There are three main features of PWM GOA circuit, (1) PWM GOA is properly designed with depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, almost all the conventional GOA schematics can only generate single pulses with fixed width [8]- [10], and are not capable of driving pixel circuits shown in Figure.1. Although, the output signals can be served as starting and resetting signals for the neighboring GOA stages with conventional circuits [11], the dynamic power consumption will be increased for the generation of complex waveforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, almost all the conventional GOA schematics can only generate single pulses with fixed width [8]- [10], and are not capable of driving pixel circuits shown in Figure.1. Although, the output signals can be served as starting and resetting signals for the neighboring GOA stages with conventional circuits [11], the dynamic power consumption will be increased for the generation of complex waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to develop a new circuit topology for GOA circuit of for AMOLEDs [12]. The GOA circuit proposed by Li et al can generate single pulses with programmable width [8]. And Cao et al reported a circuit that can produce outputs with programmable pulse width and number [9].…”
Section: Introductionmentioning
confidence: 99%